Living Qur'an: Nilai Filosofis Piil Pesenggiri Pada Tradisi Masyarakat Lampung di Kecamatan Anak Tuha - Aprina Sari; Ahmad Isnaeni; Beko Hendro (Qolamuna : Jurnal Studi Islam, 2025)
There is a tradition in Lampung that is based on the Qur’an and reflects the life principlesof the Lampung ethnic group, which are still firmly upheld to this day. This tradition existsin Anak Tuha Subdistrict, Central Lampung Regency, and is better known as piil pesenggiri.The piil pesenggiri tradition continues to exist and is preserved continuously as a guidingprinciple in the community's way of life. This study examines the practice of the livingQur’an among the people of Anak Tuha Subdistrict, Central Lampung Regency. Themethod used in this research is qualitative, including both library and field research, andemploys a phenomenological approach. To gather data, the researcher used variousinstruments such as observation, interviews, and documentation. The results show that the Lampung people already had their own philosophy—piil, meaning self-respect or dignity—even before the arrival of Islam. After Islam came, it evolved into piil pesenggiri, which includes elements such as bejuluk beadek (having a title and manners), nemui nyimah (hospitality), nengah nyappur (social interaction), and sakai sambayan (mutual cooperation). Piil pesenggiri is, in fact, relevant to the teachings of the Qur’an. However, until now, it has mostly been seen merely as a cultural tradition related to Islam, without being directly linked to specific verses of the Qur’an that convey the same values.